Dominasi Bahasa Ibu di Sekolah: Tantangan Penggunaan Bahasa Indonesia di Tingkat SMP - Marselina Ferdy Rante; Yohana Siu; Ahmad Alvian Sumarlin; Rikardus Nasa (Universitas Palan, 2026)
This study examines the dominance of mother tongue use in junior high school environments and its implications for the use of Indonesian as the language of instruction. The research is grounded in the sociolinguistic reality of multilingual Indonesian society, where students tend to rely on their first language in daily communication. The objective of this study is to analyze the factors influencing the dominance of mother tongue, its impacts on students’ Indonesian language proficiency, and its pedagogical implications. This study employs a qualitative approach using a literature review design, analyzing relevant scholarly sources published in recent years. The findings indicate that the dominance of mother tongue is influenced by linguistic, social, and psychological factors, including family environment, peer interaction, and limited Indonesian vocabulary mastery. The study reveals dual impacts: while mother tongue use facilitates comprehension and increases students’ confidence, it also potentially hinders formal Indonesian language development and leads to language interference. The study concludes that mother tongue should not be viewed solely as a barrier but as a potential pedagogical resource. The implications suggest that educators should adopt contextual bilingual strategies to optimize Indonesian language learning in multilingual classrooms.